The spirituality of wine - Kreglinger, Gisela H., 1967- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2016)
Wine serves an important role both in Scripture and in the Christian church, but its significance has received relatively little theological attention in modern times. This book fills that gap. Viewing wine as a gift of God's created bounty and as a special symbol used pervasively throughout Scripture, Kreglinger canvasses the history of wine in the church, particularly its use in the Lord's Supper, discusses the fascinating process of winemaking, and considers both the health benefits of wine and the dangers of alcohol abuse. Offering a vision of the Christian life that sees God in all things - including the work of a vintner and the enjoyment of a well crafted glass of wine.
10. Wine, Viticulture, and Soul CareConclusion; Appendix 1: Hebrew and Greek Wine Terminology in Scripture; Appendix 2: Crafting a Church Service for the Blessing of the Grapes; Notes; Bibliography; Index of Names; Index of Subjects; Index of Scripture References.
Includes bibliographical references (pages 258-269) and indexes.
Print version record.
Keywords: Wine -- Religious aspects -- Christianity; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Wine -- Religious aspects -- Christianity; Electronic books